2018
DOI: 10.1002/ab.21760
|View full text |Cite
|
Sign up to set email alerts
|

Who victimizes whom and who defends whom? A multivariate social network analysis of victimization, aggression, and defending in early childhood

Abstract: The aim of this research was to investigate the interplay between victim‐aggressor relationships and defending relationships in early childhood to test the proposition that young aggressors are less selective than older children in their choice of vulnerable targets. Cross‐sectional multivariate statistical social network analyses (Exponential Random Graph Models) for a sample of 177 preschoolers from seven classes, 5‐ to 7‐years‐old, revealed that boys were more aggressive than girls, toward both boys and gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 51 publications
4
41
1
1
Order By: Relevance
“…It was also found that, as hypothesized, in preadolescence and early adolescence, affection goals do not affect the association between status goals and direct aggression. This is in line with earlier work showing that at young ages, children seem to be able to use direct aggression without much concern for the loss of affection (Huitsing and Monks 2018). Conversely, the current findings corroborated the hypothesis that for older adolescents, status goals are more strongly associated with direct aggression, but only when youths have lower levels of affection goals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was also found that, as hypothesized, in preadolescence and early adolescence, affection goals do not affect the association between status goals and direct aggression. This is in line with earlier work showing that at young ages, children seem to be able to use direct aggression without much concern for the loss of affection (Huitsing and Monks 2018). Conversely, the current findings corroborated the hypothesis that for older adolescents, status goals are more strongly associated with direct aggression, but only when youths have lower levels of affection goals.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the period of adolescence, such parental effects are likely to be stronger in preadolescence, given the more central role of parents (Nangle et al 2003). Also in other research it was shown that children are able to use direct aggression in the peer context for the pursuit of status without much loss of affection (Huitsing and Monks 2018).…”
Section: The Changing Link Between Status Goals and Aggressionmentioning
confidence: 95%
“…Since the percentage of repeaters is the same (7.7%) in victims and bullies, it cannot be concluded that the variable repeating a year is a moderating variable to predict the victim or aggressor profile, despite the findings of other publications [49]. However, there were statistically significant differences between repeating a year and neuroticism (p = 0.043), as well as anti-social behaviour (p = 0.046).…”
Section: Discussionmentioning
confidence: 75%
“…We designed an ad hoc questionnaire in which different bullying incidents were narrated in a text illustrated with stick-figure cartoons, as used in previous research (Ortega-Ruiz et al, 2002; Monks and Smith, 2006; Huitsing and Monks, 2018). The first picture shows a situation of exclusion and had the following accompanying text: “Some children play football together every day.…”
Section: Methodsmentioning
confidence: 99%
“…The study of emotional moral attributions in younger children is very useful for the design of prevention programs adapted to moral emotions development in bullying, but requires the use of instruments adapted to them (Kutnick et al, 2007). Cartoons have been useful to measure aggressive behavior in young children (Huitsing and Monks, 2018). Likewise, although some recent studies have pointed out the moral and emotional differences in direct and indirect forms of bullying (Kokkinos and Kipritsi, 2018; Bjärehed et al, 2019), very few studies have focused on the possible differences in the emotional attribution to the victims and the different aggression types.…”
Section: Introductionmentioning
confidence: 99%